The Implementation of the Problem Based Learning (PBL) Learning Model Assisted by Canva Media in the Pancasila Education Subject on the Learning Outcomes of Grade IV Students - Swandari, Arini Dwi; Fauziah, Anna; Maharani, Tidi (Global Education Journal, 2025)
Education is very important to improve the quality and integrity of a person. This study aims to examine the completeness of student learning outcomes in the subject of Pancasila education after the implementation of the problem-based learning (PBL) learning model assisted by Canva media in grade IV of SD Negeri 59 Lubuklinggau. This study uses a quantitative method with a one-group pretest-posttest design. The population in this study was all grade IV of SD Negeri 59 Lubuklinggau. The research sample consisted of 23 students of grade IV.B selected using a random sampling method. Data collection techniques include observation, interviews, documentation, and tests. The test was conducted using an instrument in the form of multiple choices with a total of 13 questions. Data analysis techniques used were finding the average, standard deviation and hypothesis testing. The results showed an increase in the average value of students from 59.26 (pretest) to 80.04 (posttest). Hypothesis testing using the t-test produced a t-count of 5.122 greater than the t-table of 1.717, which means the hypothesis is accepted. Thus, the implementation of the PBL model assisted by Canva media has been proven to significantly improve learning outcomes and foster active student participation in learning.